Desenvolvimento de uma metodologia para a minimização de custos ambientais a partir de conceitos de simbiose industrial em redes horizontais de empresas - Mainardes, Cristiane (2017)
The objective of this work was to develop a methodology to evaluate potential actions aimed at minimizing environmental costs from the concepts of Industrial Symbiosis in horizontal networks of companies. To accomplish this objective, a Systemic Literature Review (RBS) was carried out using Methodi Ordinatio methodology, which resulted in a portfolio of 149 articles, which were used to develop the proposed methodology. With the results, it was possible to identify descriptions of environmental costs and industrial symbiosis, and later allowed the adaptation of the environmental cost model with the industrial symbiosis identification questionnaire. The methodology was applied in a cluster of dairies in the city of Piraí do Sul - PR, in three stages, being: the first stage, the data collection through a questionnaire; The second stage, to elaborate a new scenario for each company and, the third stage, the analysis of the results. However, it was possible to identify the relationship of potential of Industrial Symbiosis in the cluster, relating them to the environmental costs, thus allowing a reduction of these costs through the collaboration and trust of the members of the agglomerate.